Navigating Social Identity: A Study of Acculturation Processes among Afghan Adolescents in Yazd, Iran - Ali Ruhani; SeyedAlireza Afshani; Khadijeh Fuladi; Shakila Moradi; Bahar Amini Lari; Saba Samadian (Strategic Research on Social Problems)
IntroductionOver the past few decades, significant waves of Afghan migration have occurred, particularly to neighboring countries, such as Iran and Pakistan. This phenomenon has created substantial challenges, especially in Iran, where Afghans have resided for the last four decades. Among these challenges, adaptation and acculturation of Afghan immigrant adolescents - the second generation - to their host societies have been particularly noteworthy. Although many of these adolescents have been born in Iran, they remain actively engaged in the complex process of acculturation. Naturally, this second generation experiences a different cultural adaptation process compared to their predecessors. They face more pronounced value and cultural conflicts due to the dual influences of their parents' culture and the society in which they live. In light of this, our literature review focused on the relevant research and theories related to identity and adaptation. This theoretical sensitivity informed our research design and the development of our interview protocol. The protocol was structured to explore the methods and mechanisms of adolescent adaptation, their interactions with significant others, and their experiences within social structures. Our inquiry aimed to investigate various aspects of these adolescents' experiences, including:Advantages and disadvantages of living in IranTheir sense of belonging and concept of homelandThe meaning they attribute to 'homeland'Their cultural commonalities with Iranian societyThrough this approach, we sought to examine various adaptation patterns and adjust our interview protocol around these sensitive concepts. This methodology allowed us to delve deeply into the multifaceted acculturation process experienced by Afghan adolescents in Iran, providing insights into their unique challenges and experiences as second-generation immigrants.  Materials & MethodsThis study employed a qualitative research design, utilizing the grounded theory approach with a systematic method. The data analysis process involved open, axial, and selective coding techniques.Participants: The study sample consisted of 21 Afghan adolescents, comprising 15 males and 6 females. Participants were selected based on diverse inclusion criteria to ensure a representative sample.Data Collection: Data were collected through in-depth interviews with the Afghan adolescents. The interview protocol was designed to explore various aspects of their acculturation experiences.Ethical Considerations: The research adhered to strict ethical guidelines. Informed consent was obtained from all participants and their guardians. Confidentiality and anonymity were maintained throughout the research process.These methodological approaches were employed to enhance the rigor and credibility (validity and reliability) of the study, providing a comprehensive exploration of the acculturation process among Afghan adolescents in Iran. Discussion of Results & ConclusionThe study's findings were categorized into 15 main themes, including occupational challenges, fear of dehumanizing attitudes, destabilization due to structural discrimination, utopian expectations, and identity representation and persuasion. The core category that emerged was "identity paradoxes." Our analysis revealed that second-generation immigrant adolescents often became discouraged by the adaptation processes they faced within social structures, leading to the formation of a negative self-concept. The migration experience for this generation had significant consequences, with many adolescents encountering criminal labeling and rejection in social groups. Furthermore, these young people found themselves caught between familial expectations emphasizing their heritage identities and the pressures of assimilation, resulting in personality conflicts and anomic states. While living in Yazd provided relative security for these second-generation immigrants, they simultaneously grappled with identity paradoxes and limited access to various social domains. Afghan adolescents, having been born or lived in Iran for extended periods, had largely assimilated with Iranian culture. Their general inclination towards assimilation formed the primary current of their lives. However, this trend was met with resistance from two fronts:Afghan families, who feared their children's overidentification with Iranian cultureStructural pressures from the host societyConsequently, Afghan adolescents faced resistance in almost all social environments within Iranian society, despite their assimilationist tendencies. This study highlighted the complex interplay between individual desires for integration, familial cultural preservation, and societal barriers to full acceptance. These findings underscored the need for targeted interventions and policies to address the unique challenges faced by second-generation Afghan immigrants in Iran, particularly in navigating their complex identity formation processes and overcoming structural barriers to integration.